PENTINGNYA PELAKSANAAN ADMINISTRASI PEMBELAJARAN PENDIDIKAN JASMANI DI SMU - Sugeng Purwanto (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2006)
Physical and health education learning process in high school have not shown the teacher’scompetency. This is due to not all of the teachers equipped with the ability on physical andhealth education. Therefore, teacher’s knowledge on physical and health education mustbe put in concern to develop their ability which will impact on the effective and efficiency ofthe learning process. The success of learning process is influenced by several factors, suchas: (a) Awareness of the profession, competence and duty of teacher, (b) teacher’s ability inimplementing high school physical and health education curriculum, (c) teacher’s ability indoing administration of physical and health education learning process, (d) teacher’s abilityin creating learning method strategy, (e) teacher’s ability in implementing principals ofphysical and health education learning process, and (f) teacher’s ability in implementinglearning method of physical and health education. Keywords: learning administration, physical education